The Properties and Functions of Glial Cell Types of the Hypothalamic Median Eminence - Clayton, Richard W.; Lovell-Badge, Robin; Galichet, Christophe (Frontiers in Endocrinology, 2022)
The median eminence (ME) is part of the neuroendocrine system (NES) that functions as a crucial interface between the hypothalamus and pituitary gland. The ME contains many non-neuronal cell types, including oligodendrocytes, oligodendrocyte precursor cells (OPCs), tanycytes, astrocytes, pericytes, microglia and other immune cells, which may be involved in the regulation of NES function. For example, in mice, ablation of tanycytes (a special class of ependymal glia with stem cell-like functions) results in weight gain, feeding, insulin insensitivity and increased visceral adipose, consistent with the demonstrated ability of these cells to sense and transport both glucose and leptin, and to differentiate into neurons that control feeding and metabolism in the hypothalamus. To give a further example, OPCs in the ME of mice have been shown to rapidly respond to dietary signals, in turn controlling composition of the extracellular matrix in the ME, derived from oligodendrocyte-lineage cells, which may contribute to the previously described role of these cells in actively maintaining leptin-receptor-expressing dendrites in the ME. In this review, we explore and discuss recent advances such as these, that have developed our understanding of how the various cell types of the ME contribute to its function in the NES as the interface between the hypothalamus and pituitary gland. We further highlight areas of research that might uncover additional, perhaps even unappreciated aspects of the role of the median eminence and the stem and progenitor cells it contains.